1994
DOI: 10.1007/bf00187351
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of lymphoceles following kidney transplantation by intraperitoneal fenestration and omentoplasty

Abstract: The recent development of endoscopic surgery and its use in treating several abdominal and thoracic surgical pathologies lead us to suggest its application in the treatment of posttransplant lymphoceles. The authors report two cases treated by the laparoscopic approach. Recurrence occurred in one of them. The technique is described and its place among other therapeutic modalities is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…The operative strategy is to perform a peritoneal fenestration through a laparotomy, minilaparotomy, or via a laparoscopic approach. Some authors suggest the use of an omentum ap to decrease the risk of lymphocele relapse, but others do not [3±5, 14,30]. Recently, laparoscopic fenestration of posttransplant lymphoceles has been reported in the literature (Table 4) [1,6,8,9,11,15,16,19,25,28,31,32,36,38].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The operative strategy is to perform a peritoneal fenestration through a laparotomy, minilaparotomy, or via a laparoscopic approach. Some authors suggest the use of an omentum ap to decrease the risk of lymphocele relapse, but others do not [3±5, 14,30]. Recently, laparoscopic fenestration of posttransplant lymphoceles has been reported in the literature (Table 4) [1,6,8,9,11,15,16,19,25,28,31,32,36,38].…”
Section: Discussionmentioning
confidence: 95%
“…Several attempts have been made to increase the eciency of drainage, but none of these alternative approaches have found widespread acceptance. For instance, most authors do not routinely use omental packing, although it is said to improve results in terms of successful drainage and helps to avoid internal hernias [3,30]. Hsu et al [16] reported on 81 patients from nine institutions who underwent a laparoscopic lymphocele fenestration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical procedures are greatly facilitated by the increased visibility it affords; however [9], greater skill is required and the performance of such operations is more demanding than open surgery [5]. Therefore, experience in both approaches is mandatory, particularly in case conversion is needed.Training in laparoscopic surgery is usually obtained by performing phantom operations using a pelvic trainer, by doing experimental surgery or by practicing on cadavers [15]; more recently, virtual reality technology has also been applied to surgical training [20].The laparoscopic approach has been used in cadavers to practice certain abdominal procedures [1,2,6,7,10,13,14,16,17], for necropsies [3,8], for experimental purposes [10], and also to teach anatomy [12].With some exceptions, rigor mortis in embalmed cadavers has been considered a limiting factor during the creation of the pneumoperitoneum [14,17]. Certain procedures have been devised to manage this problem, such as ethanol and glycerin injections in the femoral vein with vigorous abdominal massage [10,16], insufflation with compressed air [18], gasless laparoscopy with an abdominal lifter [7], and abdominal wall resection [13].…”
mentioning
confidence: 99%